Mechanisms and machines kinematics, dynamics, and synthesis - Stanišić, M. M. (Cengage Learning, 2015)
Suitable for the mechanisms and machines course, targeting junior level mechanical engineering students. This book provides a complete, yet concise, text that can be covered in a single-semester course.